A generic model for guiding learners in adaptive hypermedia - Hafidi, Mohamed; Bensebaa, Taher; Trigano, Philippe (INFOCOMP Journal of Computer Science, 2011)
Learners often find themselves in situations where they want to achieve a goal but do not have the sufficient knowledge to enable them to achieve it spontaneously. These situations are referred to problems. Indeed, guiding a learner in a learning activity is a complex task with no guarantee of success. If the learner is not guided in performing the task, the learning objective is often not achieved, and the learning does not occur. In our work, the relevance of the guide will be on the learner’s prior knowledge and purpose of apprenticeship referred. Our approach relies on the domain model, pedagogical activities as well as the traces and inference on them. Their use allows the learner modeling and its management by the system.